Experimental study on a de-noising system for gas and oil pipelines based on an acoustic leak detection and location method. (March 2017) - Liu, Cuiwei; Li, Yuxing; Fang, Liping; Xu, Minghai
Abstract: To protect the pipelines from significant danger, the acoustic leak detection and location method for oil and gas pipelines is studied, and a de-noising system is established to extract leakage characteristics from signals. A test loop for gas and oil is established to carry out experiments. First, according to the measured signals, fitting leakage signals are obtained, and then, the objective signals are constructed by adding noises to the fitting signals. Based on the proposed evaluation indexes, the filtering methods are then applied to process the constructed signals and the de-noising system is established. The established leakage extraction system is validated and then applied to process signals measured in gas pipelines that include a straight pipe, elbow pipe and reducing pipe. The leak detection and location is carried out effectively. Finally, the system is applied to process signals measured in water pipelines. The results demonstrate that the proposed de-noising system is effective at extracting leakage signals from measured signals and that the proposed leak detection and location method has a higher detection sensitivity and localization accuracy. For a pipeline with an inner diameter of 42 mm, the smallest leakage orifice that can be detected is 0.1 mm for gas and water and the largest location error is 0.874% for gas and 0.176% for water. Graphical abstract: Highlights: Three evaluation indexes are proposed: SNR, RMSE and ALPD. The de-noising system is established in the gas and oil pipelines. The established system is used for gas pipeline effectively, including interference pipes. The established de-noising system is used for water pipeline effectively.